Spread of Giardiasis Among Children In Al-Nassiria city southern Iraq - Falih Hassen, Talib (University of Thi-Qar Journal of Science, 2009)
Over –12 month period from January 2006 to December 2006 , 898 cases of Giardiasis were diagnosed in Al-Nassiria city- Southern Iraq . The age of subject ranged from below one year to ten years. The prevalence rate of giardiasis among male significantly higher than among female (55.1%) and (44.9%) respectively . The high rate of infection with Giardia lamblia 125 (93.3%) cases in children (1—2) years old , Also result revealed that the cyst phase was dominant (61.6%) than trophozoite (38.3%) . Mixed infections showed double infections with Giardia lamblia 56(62.3%) .The common symptoms was diarrhoea (94.1%) and the highest rate of infection were in summers months .